Impacts of COVID-19 on the schedule of elective surgery (Research, Society and Development, 2022)
The operative moment is related to the specificity of the procedure, the indication to treat a clinical condition, the advantages and disadvantages of waiting in relation to the patient's conditions, as well as the evolution of the patient's condition. The operative moment can be subdivided into emergency, urgent or elective procedures. Specifically considering the health care activity, the situation experienced by the population in 2020 left the lack of information available to compare and project the cause and effect of the interruption of surgeries in public health, also affecting elective surgeries. This is an integrative review, with a qualitative approach, exploratory and descriptive. The collection period was from March to August 2021 from the Publisher Medline (PUBMED) databases using the Medical Subject Headings (MeSH): "Health Services Accessibility", "Coronavirus Infections", "Elective Surgical Procedures" and the Descriptors in Health Sciences (DeCS), namely: "Access to Health Services", "Coronavirus Infections" and "Elective Surgical Procedures". In order to expand the sample, a second strategy of combining descriptors was adopted in the Latin American and Caribbean Literature on Health Sciences databases (LILACS) and in MEDLINE by the Virtual Health Library (BVS) using only two of the Medical Subject Headings (MeSH): “Coronavirus Infections” and “Elective Surgical Procedures” combined with each other using the Boolean operator “AND”. A total of 1247 articles were found. After applying these criteria, 12 studies were selected to compose the review. We can conclude that the coronavirus had a negative impact on elective surgeries, many patients continued with their pathologies or aesthetic desires to perform their surgeries without power, many surgeons mainly of aesthetic plastics stopped their services for a while in order to save expenses in the period of suspension.